Modeling the function of BAX and BAK in early human brain development using iPSC-derived systems - Joshi, Piyush (Cell Death Dis, 2020)
Intrinsic apoptosis relies on the ability of the BCL-2 family to induce the formation of pores on the outer mitochondrial membrane. Previous studies have shown that both BAX and BAK are essential during murine embryogenesis, and reports in human cancer cell lines identified non-canonical roles for BAX and BAK in mitochondrial fission during apoptosis. BAX and BAK function in human brain development remains elusive due to the lack of appropriate model systems. Here, we generated BAX/BAK double knockout human-induced pluripotent stem cells (hiPSCs), hiPSC-derived neural progenitor cells (hNPCs), neural rosettes, and cerebral organoids to uncover the effects of BAX and BAK deletion in an in vitro model of early human brain development. We found that BAX and BAK-deficient cells have abnormal mitochondrial morphology and give rise to aberrant cortical structures. We suggest crucial functions for BAX and BAK during human development, including maintenance of homeostatic mitochondrial morphology, which is crucial for proper development of progenitors and neurons of the cortex. Human pluripotent stem cell-derived systems can be useful platforms to reveal novel functions of the apoptotic machinery in neural development.